Prenatal diagnosis of fetal adrenal cystic neuroblastoma - Torres-Cepeda, Duly (2022)
Neuroblastoma is an embryonal tumor arising from neuroblasts (pluripotentsympathetic cells) and is the most common malignant solid lesion in childhood. Thesetumors can arise anywhere in the fetal sympathetic nervous system, but the adrenalgland is affected in 90% of cases during the prenatal period. Cystic neuroblastomascomprise about 50% of all cases diagnosed in fetuses and their frequency is evenhigher in the postnatal period. Ultrasonography can be used to determine thesize, location, and sonographic features of the tumor. Fetal MRI can be useful forstaging and evaluation of metastases. Management of pregnancy is expectant andtermination of pregnancy is rarely indicated. A case of prenatal diagnosis of fetaladrenal cystic neuroblastoma is presented.